The Forbidden Foods in The Light of Surat Al-Māʼidah And Their Relationship with The Coronavirus Disease 2019: An Analytical Study - Bey Zekkoub, Abdelali (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Allāh Almighty has sent down the noble Qur’ān to be a guidance and a way of life for all mankind, and He has enacted in its rules and commandments that are used to preserve the religion, Life, Intellect, Lineage, and Property. The problem of this research arises that some people are indifferent to the physical and psychological harm resulting from their consumption of forbidden foods. Hence, this research tries to shed light on the types of forbidden foods within the frame of Surat Al-Māʼidah for verses (3, 90, 95, 96) and find out their relation with the infection of the Coronavirus Disease 2019 (COVID-19). To investigate this topic, this study uses the inductive, analytical and the deductive approaches. The findings presented in this article are the outcomes of a thematic analysis of Qur'ānic verses related to the forbidden foods. The study identifies five types of forbidden foods: (1) The slaughtering animals not in accordance with Sharia Law, (2) The uses and the drinking of the fresh blood, (3) The consumption of any product contains any element of Pork, (4) All Alcoholic beverages and (5) Any scarified animals not meant to Allāh Almighty. Besides, it comes to conclude that many physical diseases and psychological disorders stem from the consumption of forbidden foods; such as a weak immune system, high or low blood pressure, cancer, liver damage, kidney problems, high cholesterol, psychological problems, depression, despair, anxiety, stress, and so forth. Therefore, this study will contribute to revealing the high positive relationship between diseases resulting from consuming forbidden foods and the grave cases of people infected with Covid-19. Finally, it suggests to spread more awareness towards the Ḥalāl logo in Muslim communities and around the world; to maintain the use of Ḥalāl food, which is in the interest of oneself and society.